Eurycoma Longifolia Jack (Tongkat Ali) extract reduces the growth of salivary isolated Streptococcus mutans and Lactobacillus - Ramzi, Muhamad Iyad; Kosnin, Muhammad Hazzim; Faisal, Ghasak Ghazi; Arzmi, Mohd Hafiz; Kusumawardani, Anisa (2019)
Introduction: The roots of E. longifolia or Tongkat Ali is well known in traditional medicine and have wide spectrum of biological activity including antibacterial properties. The objectives of this study were to investigate the effect of the E. Longifolia root extracts on the growth of Streptococcus mutans and Lactobacillus isolated from saliva of adult patients with high caries risk. Materials and methods: The ethanolic extract of the root of this plant was tested against saliva isolated Streptococcus mutans and Lactobacillus via disc diffusion assay at a concentration of 200mg/mL. The minimum inhibitory concentration was carried out by the standard broth microdilution method. Results: Disk diffusion assay showed positive zones of inhibition for all test microorganisms with S. mutans, Lactobacillus exhibiting zones of inhibition of 8.3 ± 0.7mm, 12.4 ± 2.4mm respectively. For minimum inhibitory concentration, the test microorganisms were tested at concentration of 250mg/mL, 125mg/mL, 62.5mg/mL, 31.3mg/mL and 0mg/mL. The minimum inhibitory concentration showed that MIC of S. mutans was at 62.5mg/mL, Lactobacillus at 125mg/mL. Conclusion: Ethanol-based E. longifolia Jack root extract has an antimicrobial effect on S. mutans and Lactobacillus which gives this extract the potential to be used in oral health preparations such as toothpastes and mouthwashes.